Absolute hand determination of glycofibrils from natural sources in cryo-EM - Qi Zhang; Lanju Qin; Tongtong Wang; Zhangqiang Li; Yilin Zhang; Sheng Chen; Qijun Ge; Jialing Wen; Nieng Yan; Jiawei Wang; Mingxu Hu (Proceedings of the National Academy of Sciences, 2026)
Glycans are not only one of the four fundamental macromolecular classes that constitute life, but also the most abundant among these four across the Earth. However, compared with proteins and nucleic acids, our understanding of the structures and functional mechanisms of glycans remains limited. Moreover, it is generally challenging to obtain high-resolution three-dimensional structures of glycans. Recent studies have demonstrated the potential of the CryoSeek strategy in enabling high-throughput structural determination of glycans, thereby presenting novel avenues for their structural investigation. Meanwhile, unlike proteins, near atomic resolution density maps of glycofibrils do not inherently facilitate the determination of absolute hand, which is a prerequisite for building atomic models of glycofibrils. Existing absolute hand determination methods have severe limitations in the case of glycofibrils from natural sources. In this study, we introduce Ahaha, a straightforward and efficient method for determining such absolute hand in cryogenic electron microscopy. With their absolute hand measured by Ahaha, we built atomic models of four glycofibrils derived from a natural water sample, facilitating the study of glycans. The online service of Ahaha is available at https://cryoseek.org/ahaha .